2018
DOI: 10.15835/nbha46110743
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salicylic Acid and Calcium Nitrate Spraying on Qualitative Properties and Storability of Fresh Jujube Fruit (Ziziphus jujube Mill.)

Abstract: Chinese jujube is among the important medicinal plants grown in Iran. Its valuable fruit have a short post-harvest life. Delaying of quality reduction for few days can help maintaining the shelf life of fresh jujube fruit. The current study was conducted to investigate the possible effects of pre-harvest foliar application of salicylic acid (0, 2 and 4 mM) and calcium nitrate (0, 1 and 2%) on physico-chemical characteristics and shelf life of fresh jujube fruit during storage at 10-days intervals, for 40 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…Maximum (120.05 mg/100 g) total phenolic content was recorded in calcium nitrate @0.50% followed by calcium nitrate @0.25% (117.90 mg/100 g) whereas minimum (103.02 mg/100 g) was reported in control. These results were harmony with the findings of Zeraatgar et al (2018) who reported increased in total phenolic content of jujube fruit with application of 1% calcium nitrate over control. The reason for higher total phenolic content with the foliar application of calcium nitrate may be due to fact that calcium compounds strengthen cell walls, maintains as well as control selective exchange of gas and ion.…”
Section: Methodssupporting
confidence: 90%
“…Maximum (120.05 mg/100 g) total phenolic content was recorded in calcium nitrate @0.50% followed by calcium nitrate @0.25% (117.90 mg/100 g) whereas minimum (103.02 mg/100 g) was reported in control. These results were harmony with the findings of Zeraatgar et al (2018) who reported increased in total phenolic content of jujube fruit with application of 1% calcium nitrate over control. The reason for higher total phenolic content with the foliar application of calcium nitrate may be due to fact that calcium compounds strengthen cell walls, maintains as well as control selective exchange of gas and ion.…”
Section: Methodssupporting
confidence: 90%
“…Preharvest application of salicylic acid maintains apple fruit physicochemical quality through increasing the action of antioxidant enzyme and total phenols content (Supapvanich, Mitsang, & Youryon, 2017). The researchers demonstrated that the use of salicylic acid (4 mM) significantly improved the postharvest quality of Chinese jujube ( Ziziphus jujube Mill) fruit (Zeraatgar, Davarynejad, Moradinezhad, & Abedi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…At the end of 35 days of storage period fruits received two sprays Ca(NO ) @ 2.0 % recorded 8.38 % higher phenolics content 3 2 in comparison to control fruits. This signifies the efficacy of two sprays Ca(NO ) @ 2.0 % in maintaining the phenolics 3 2 content as calcium compounds strengthen the cell walls, maintains the selective exchange of ions and gases (Zeraatgar et al 2018), prevents the leaching of polyphenol compounds, therefore causing reduction in the oxidation of phenols (Turmanidze et al 2016). Reducing and non-reducing sugars: Sugars have a critical role in determining the palatability of the fruits.…”
Section: Resultsmentioning
confidence: 99%